MAKNA TARI BUCERAI KASIH DALAM PESTA PERKAWINAN DI DESA RANTAU PANDAN KECAMATAN RANTAU PANDAN KABUPATEN BUNGO PROVINSI JAMBI - Abd Rohman Hasan; Desfiarni Desfiarni; Zora Iriani (FBS Universitas Negeri Padang, 2018)
Abstract This study was aimed to describe and analyze meaning of Bucerai Kasih dance on wedding party in Desa Rantau Pandan Kecamatan Rantau Pandan Kabupaten Bungo Provinsi Jambi. Type of this study was qualitative approach with using analytical descriptive method. Type of data in this study were both primary and secondary. Data were collected by using library research, observation, interview and documentation. The study object was Bucerai Kasih dance on wedding party in Desa Rantau Pandan Kecamatan Rantau Pandan Kabupaten Bungo Provinsi Jambi. Result of this study showed that Bucerai Kasih dance was a traditional dance as the embodiment of the values of society’s daily life in Desa Rantau Pandan. It was about responsibility in living acitvies on the wedding party. The meaning of Bucerai Kasih dance which was seen in aspect of motion were spirit and working hard to keep on living. Besides, in floor pattern aspect, it could be seen that there were solidarity and team work attitudes. Then, in some tools namely properties was meant like each other sign inter the dancer. Costum was meant identity of malay and music was namely song lyric was meant worry of youth who were afraid in separating from love. Moreover, meaning of the dance on wedding party was a warning for the youth that in building of household was not easy. Performance of this dance gave satisfaction to the audicences and people who had celebration and it contained of social values namely teamwork, responsibilty and respect each other which were as the identity and the harmony of life of Desa Rantau Pandan’s society. Keywords: Meaning of Dance, Bucerai Kasih Dance, The Wedding Party